2006
DOI: 10.7863/jum.2006.25.6.701
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram of Fetal Lung Volumes Estimated by 3‐Dimensional Ultrasonography Using the Rotational Technique (Virtual Organ Computer‐Aided Analysis)

Abstract: A new nomogram of fetal lung (right, left, and total) volumes throughout gestational age using the rotational technique (VOCAL) is described, and reference values have been generated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
4
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 25 publications
8
56
4
10
Order By: Relevance
“…2 a) and the ipsilateral lung volumes of right-sided CDH cases in the nomogram of the right fetal lung volumes ( fig. 2 b) [26] . It was not possible to identify the ipsilateral lungs to the diaphragmatic defect in 6 (19.4%) fetuses (4 left-sided CDH and 2 rightsided CDH) and the ipsilateral lung volumes were considered equal to 0.01 cm 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 a) and the ipsilateral lung volumes of right-sided CDH cases in the nomogram of the right fetal lung volumes ( fig. 2 b) [26] . It was not possible to identify the ipsilateral lungs to the diaphragmatic defect in 6 (19.4%) fetuses (4 left-sided CDH and 2 rightsided CDH) and the ipsilateral lung volumes were considered equal to 0.01 cm 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The ipsilateral lung volumes were compared to nomograms of right and left pulmonary volumes previously described [26] , and the observed/expected ipsilateral lung volume ratios (o/e-Ipsi-FLVR) were then calculated. Correlations between the o/e-Ipsi-FLVR, the o/e-TotFLVR and the LHR were analyzed by Pearson correlation test (SPSS 14, Microsoft, USA).…”
Section: Discussionmentioning
confidence: 99%
“…The spectrum of these malforma- tions can range from those with excellent neonatal prognosis to lethal conditions such as bilateral renal agenesis or infantile polycystic disease. Three-dimensional US offers a more accurate volumetric estimation of fetal organs than 2D-US [14,15] , thus allowing a better assessment of growth. In a recent study, Chang et al [8] reported that RV estimated by the multiplanar method was a good predictor of intrauterine growth restriction (using the 10th percentile as a cut-off), with a sensitivity of 96.4%, a specificity of 95.9%, a positive predictive value of 75.0% and a negative predictive value of 99.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Contralateral lung volume was compared with nomograms of right and left pulmonary volumes published previously, 22 and the observed/expected contralateral lung volume ratio (o/eContFLVR) was calculated and compared with the lung/head ratio (LHR), observed/expected total fetal lung volume ratio (o/e-TotFLVR), and neonatal outcome. Correlation between the o/eContFLVR, o/e-TotFLVR, and LHR was analyzed by Pearson correlation test (SPSS for Windows version 14, Microsoft Corporation, Chicago, IL, USA).…”
Section: Methodsmentioning
confidence: 99%